Monascus purpureus-fermented Thai glutinous rice reduces blood and hepatic cholesterol and hepatic steatosis concentrations in diet-induced hypercholesterolemic rats - Bunnoy,A. (BioMed Central, 2015)
© Bunnoy et al. Background: Red yeast rice (RYR) is a fermented product used as a food supplement to promote blood circulation and lower blood cholesterol levels in eastern Asia. Interestingly, monacolin K is the most active compound in RYR that proved to inhibit HMG-CoA reductase in the cholesterol biosynthesis pathway. Methods: The hypocholesterolemic effects of oral administration of Thai RYR, produced by fermentation of Thai glutinous rice (Oryza sativa L. var. Niaw San-pah-tawng) with Monascus purpureus CMU 002U, were determined in normal and hypercholesterolemic rats. The rats were divided into six groups, and fed two different kinds of diet. Groups I-II, normal rats fed with a normal diet (SP-diet), were treated with distilled water (SP-control) and 2.0 g/kg/day of RYR extract (SP-2 g). In Groups III-VI, the rats were rendered hypercholesterolemic by feeding them a high fat and cholesterol diet (HFC-diet), and were treated with distilled water (HFC-control), 1.0 g/kg/day (HFC-1 g), 2.0 g/kg/day (HFC-2 g) of RYR extract, and 5.0 mg/kg/day of rosuvastatin (HFC-rosuvastatin) for 30 days, respectively. Results: The RYR extract significantly decreased the concentrations of serum total cholesterol and low density lipoprotein cholesterol (LDL-C), atherosclerotic index, LDL-C/HDL-C ratio and hepatic cholesterol levels in both HFC-1 g and HFC-2 g groups (p < 0.05) as compared with the HFC-control group, and with no significant change in high density lipoprotein cholesterol (HDL-C) concentrations among all six groups. The reduction of serum TC and LDL-C also paralleled the observed changes in mRNA expressions of the genes involved in cholesterol biosynthesis and homeostasis in the liver. The hypercholesterolemic rats treated with RYR extract were significantly higher in LDLR and HMGR expression, but lower in CYP7A1 expression when compared to the untreated hypercholesterolemic rats (HFC-control) (p < 0.05). The hepatic injuries in hypercholesterolemic rats were also obviously alleviated by RYR extract. Conclusions: The extract of Thai RYR possessed potent hypocholesterolemic and anti-atherogenic activities in diet-induced hypercholesterolemic rats. The possible mechanism involving cholesterol-lowering potential of the extract might contribute to its ability to increase LDL-C endocytosis in hepatocyte and to competitively inhibit HMG-CoA reductase, a key enzyme for cholesterol biosynthesis in liver.